The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1246/bcsj.70.2737
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Stabilities and Reactivities of Tris- and Bis(2,4,6-trimethoxyphenyl)carbenium Salts

Abstract: 2,4,6-Trimethoxyphenyllithium, Φ′Li[Φ′ = 2,4,6-(MeO)3C6H2], reacted with diphenyl carbonate and with ethyl formate to give tris(2,4,6-trimethoxyphenyl)methanol, Φ′3COH (1), and bis(2,4,6-trimethoxyphenyl)methanol, Φ′2CHOH (2), respectively. Compound 1 reacted with a slight excess of perchloric acid in 2-propanol to give very dark-purple crystals of the triarylcarbenium salt, [Φ′3C]X (3, X = ClO4), which were inert even in hot ethanol. However, a treatment of 3 (X = Cl), prepared in situ in 1 M (1 M = 1 mol dm−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Recently, it has been shown that readily prepared tris(2,4,6‐trimethoxyphenyl) methyl ( 1 ) and tris(2,6‐dimethoxy‐ phenyl)methyl ( 2 ) carbenium ions18–22 react with alkyl amines to generate very stable, permanently charged, nitrogen‐containing carbocations. The products, that result from sequential S N Ar reactions of methoxy substituents by the nucleophilic amines, can be studied—along with their derivatives—for photochemical, photophysical, electrochemical, stereochemical, topological and synthetic applications 18–33 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, it has been shown that readily prepared tris(2,4,6‐trimethoxyphenyl) methyl ( 1 ) and tris(2,6‐dimethoxy‐ phenyl)methyl ( 2 ) carbenium ions18–22 react with alkyl amines to generate very stable, permanently charged, nitrogen‐containing carbocations. The products, that result from sequential S N Ar reactions of methoxy substituents by the nucleophilic amines, can be studied—along with their derivatives—for photochemical, photophysical, electrochemical, stereochemical, topological and synthetic applications 18–33 …”
Section: Resultsmentioning
confidence: 99%
“…In the particular case of air‐ and moisture‐stable [ 1 ][BF 4 ], primary and secondary alkyl amines substitute effectively one, two or even three para ‐methoxy substituents of the carbenium ion in a polar solvent (DMF, acetonitrile) at room temperature 18–22. However, as a significant decrease in reactivity follows each consecutive substitution, it is generally facile to substitute a single p ‐MeO group of 1 by using a lone equivalent of amine and a short reaction time (shown in Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2) [17]. Starting from the readily available tris(2,4,6-trimethoxyphenyl)methylium salt (TMP) 3 C + [18,29], stepwise replacement of the para- methoxy groups by dialkylamines provides access to a wide variety of symmetric and asymmetric triarylmethylium dyes [18,3031]. Replacement of two o- methoxy groups by one primary amine gives acridinium-type ring systems (Fig.…”
Section: Introductionmentioning
confidence: 99%